Efek Metode Peta Konsep dalam Pembelajaran Inkuiri Terbimbing terhadap Keterampilan Proses Sains Siswa - I Putu Artayasa; Muhlis Muhlis; Gito Hadiprayitno; I Wayan Merta (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Science process skills include cognitive and psychomotor skills that can contribute to helping students learn facts, concepts, principles, or theories, so that students can effectively study science. This research was conducted to examine whether there is an effect of implementing the concept map method in guided inquiry learning on students' science process skills. The study was conducted with an Intact Group Comparison design. The research subjects were junior high school students in Mataram City. The research took place in the even semester of the 2020/2021 academic year. Purposive sampling technique was applied to obtain a sample of 91 individual students from two junior high schools. The results showed that, students who implemented concept map preparation during guided inquiry learning had a higher science process skill score than students who applied guided inquiry learning, but did not make concept maps and conventional class students. The conclusions of this study indicate that the preparation of concept maps in guided inquiry learning has a significant effect on students' science process skills. Based on these conclusions, it is recommended that educators try to apply guided inquiry learning, accompanied by assignments to make concept maps.